Handling Student Bullying by Using Islamic Education Based on Multicultural Understanding - Muksin, Muksin (Universitas Negeri Makassar, 2025)
Bullying in schools is a serious problem that affects students’ emotional stability, social relationships, and academic achievement. In multicultural societies, differences in ethnicity, religion, culture, and language often trigger misunderstanding and conflict, which may escalate into bullying behavior. This study aims to analyze the implementation of Islamic education based on multicultural understanding as an effort to handle bullying among students. The research was conducted at Al-Ibrohimy Galis Bangkalan and Al-Amien Prenduan Sumenep Islamic Boarding Schools. This study employed a qualitative method with a case study design, involving data collection through observation, interviews with teachers and students, and documentation of educational activities. Data analysis was carried out through data reduction, display, and verification to ensure the validity of the findings. The results reveal that multicultural-based Islamic education can effectively reduce bullying by fostering values of tolerance, empathy, and mutual respect among students. Teachers play an essential role in modeling inclusive attitudes and integrating multicultural values into the curriculum and daily learning activities. The conclusion shows that Islamic education emphasizing multicultural understanding creates a safer, more harmonious, and cooperative school environment. The implications of this study highlight the importance of continuous teacher training on bullying prevention and conflict resolution, as well as the integration of multicultural education across all subjects. Further research is recommended to examine the long-term impact of multicultural Islamic education in reducing bullying and promoting peace-oriented character formation among students.